Apolipoprotein E mimetic peptide CN-105 improves outcome in a murine model of SAH. Issue 4 (4th September 2018) - Liu, Ji; Zhou, Guanen; Kolls, Bradley J; Tan, Yanli; Fang, Chuan; Wang, Haichen; Laskowitz, Daniel T
Abstract : Objective: Subarachnoid haemorrhage (SAH) accounts for 3% of all strokes, and is associated with significant morbidity and mortality. There is growing evidence implicating apolipoprotein E (apoE) in mediating adaptive anti-inflammatory and neuroprotective responses following ischaemic and traumatic brain injury. In the current study, we test the efficacy of a small apoE mimetic peptide, CN-105 in a murine model of SAH. Methods: Mice subjected to SAH received repeated intravenous injections of CN-105 every 12 hours for 3 days, with the first dose given 2 hours after injury. Daily functional outcomes were assessed by rotarod and neurological severity score. Haemorrhage grade and cerebral vascular diameters were measured at 5 days post-SAH. Cerebral microgliosis, neuronal degeneration and survival were analysed at 5 and 35 days post-SAH, respectively. Results: CN-105 reduces histological evidence of inflammation, reduces vasospasm and neuronal injury and is associated with improved long-term behavioural outcomes in a murine model of SAH. Conclusions: Given its favourable pharmacokinetic profile, central nervous system penetration and demonstration of clinical safety, CN-105 represents an attractive therapeutic candidate for treatment of brain injury associated with SAH.